Mind the Gap! Populism, Participation and Representation in Europe. Issue 4 (4th November 2017) - Huber, Robert A.; Ruth, Saskia P.
Abstract: This article assesses the influence of populist parties on two central aspects of democracy – participation and representation. In line with traditional theories on populism and democracy, we argue that populist parties have a positive effect on electoral turnout and the equality of participation. This effect, however, is moderated by the party's role in government or opposition as well as their host‐ideology, i.e. left, centre or right. We argue that populist parties also have a positive effect on substantive representation, but that this effect is strongly dependent on their host‐ideology. We test these arguments with lagged dependent variable models using data from 31 European countries from 1990 until 2014. We find mixed support for our theoretical expectations.